2015
DOI: 10.1542/peds.2014-3973
|View full text |Cite
|
Sign up to set email alerts
|

Early Career Experiences of Pediatricians Pursuing or Not Pursuing Fellowship Training

Abstract: BACKGROUND AND OBJECTIVES: Choosing career paths can be difficult decisions for residents contemplating fellowship training. This study compares the experiences of early career pediatricians who did and did not pursue fellowships. METHODS: We analyzed national, weighted data from pediatricians 8 to 10 years after residency (n = 842). Work environment, work–life balance, and satisfaction were compared for pediatricians who had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…A total of 4,018 studies were identified by the initial search, 580 were identified for full-text review, and 102 1,8,10,11,18,19,24–119 were included in the final analysis (Figure 1 and Supplemental Digital Appendix 2 at http://links.lww.com/ACADMED/B493). Table 1 summarizes the key characteristics of the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 4,018 studies were identified by the initial search, 580 were identified for full-text review, and 102 1,8,10,11,18,19,24–119 were included in the final analysis (Figure 1 and Supplemental Digital Appendix 2 at http://links.lww.com/ACADMED/B493). Table 1 summarizes the key characteristics of the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…A current appropriate work-life balance was reported by 43% among young pediatricians in the USA, for whom three factors (good health, support from colleagues, and sufficient resources for care) were independently associated with greater professional satisfaction, greater personal satisfaction, and a lower prevalence of burnout ( 13 ). Others US studies reported that both pediatricians pursuing or not pursuing fellowship training can achieve overall life and career satisfaction ( 14 ), and that a large majority of pediatric subspecialists found initial jobs matching their goals for professional responsibilities and clinical care ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…7 The 19 and regardless of the decision to subspecialize, surveys of pediatricians demonstrate that most are satisfied with their careers. 20 Trainees can use this analysis as a framework to understand the financial effects of additional training as well as to understand the impact of educational debt. Medical educators could consider including basic financial concepts as part of medical school and residency curricula to increase financial literacy among physicians.…”
Section: Figurementioning
confidence: 99%